2017
DOI: 10.1002/acs.2833
|View full text |Cite
|
Sign up to set email alerts
|

Robust time‐varying Kalman estimators for systems with packet dropouts and uncertain‐variance multiplicative and linearly correlated additive white noises

Abstract: SummaryThis paper is concerned with robust estimation problem for a class of time-varying networked systems with uncertain-variance multiplicative and linearly correlated additive white noises, and packet dropouts. By augmented state method and fictitious noise technique, the original system is converted into one with only uncertain noise variances. According to the minimax robust estimation principle, based on the worst-case system with conservative upper bounds of uncertain noise variance, the robust time-va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The proposed results expand the research of robust Kalman estimation problem for system with mixed uncertainties in the literature, such as the uncertain noise variances are not considered in References 29,30, the only single networked‐induced uncertainty is considered in References 31–33, the random measurement delay, 34 the packet dropouts, 35,36 and missing measurement 37 are not considered. The robust FCI fusion Kalman estimation problem is seldom considered.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The proposed results expand the research of robust Kalman estimation problem for system with mixed uncertainties in the literature, such as the uncertain noise variances are not considered in References 29,30, the only single networked‐induced uncertainty is considered in References 31–33, the random measurement delay, 34 the packet dropouts, 35,36 and missing measurement 37 are not considered. The robust FCI fusion Kalman estimation problem is seldom considered.…”
Section: Discussionmentioning
confidence: 87%
“…A minimum variance estimator for multisensor system with random parameter, one‐step measurements delay and packet dropouts is proposed in Reference 30. Following Reference 16, the robust Kalman estimation problem for system with uncertain noise variance, multiplicative noise and single networked‐induced uncertainty are addressed in References 31–33, where packet dropouts 31,32 and one‐step measurements delay 33 are considered respectively. Further, the robust fusion Kalman estimation problem for system with two networked‐induced uncertainties are addressed in References 34–37, where missing measurements and packets dropouts, 34 random measurements delay and missing measurements, 35,36 random measurements delay and packets dropouts 37 are considered, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The system given in ( 1), ( 2), (12), and ( 14) can be equivalently written in an augmented form. Let us consider a new state vector as follows:…”
Section: Augmented Stochastic State-space Modelmentioning
confidence: 99%
“…From Figure 2, it is observed that there are 25 instants at which event have not occurred. Thus, sensor data are not transmitted for these instants and the estimator uses previous data available in the estimator node according to (12). This ensures that the bandwidth utilization and F I G U R E 2 Occurrence of event: "1" represents event has occurred, whereas "0" indicates event has not occurred.…”
Section: Consider the System With Matrix In (1) And (2) As Followsmentioning
confidence: 99%
See 1 more Smart Citation